Technology integration and pedagogical innovations in Malaysian higher education institutions / Lu Huong Ying - Lu, Huong Ying (2013)
The gap between massive educational technology investments and the expected return in enhancing teaching and learning is a global education agenda. Education reform waves have called for a wider review of pedagogical innovations in education systems around the world. The primary purpose of this study was to examine the relationships between technology integration practises and pedagogical innovations in the contexts of Malaysian higher education institutions. In this study, technology integration practice was the independent variable whereas pedagogical innovation was the dependent variable. Demographic profiles specified by six indicators were chosen as moderating variables. A total of 248 faculty members from six Tier 5 higher education institutions in Malaysia participated in this study with a response rate of 40.6%. Three of the higher education institution institutions are public universities and the remaining three are private universities. This study adopted a simple random sampling procedure of data collection using questionnaire administered through assistant faculty registrars and also through online survey. Data collected was first analysed for descriptive such as mean, standard deviation and percentage. This was followed by inferential statistics such as t-test, one-way ANOVA, UNIVARIATE, Pearson Correlation tests, and regression analyses to examine the relationships among the variables. The fidelity levels of technology integration practices were examined using an adapted innovative configuration component map. Seventy percent of the subjects had high fidelity level of technology integration practises. Pedagogical innovation was examined using an adapted instrument based on the SITES-M2 findings. It was revealed that subjects had pedagogical innovativeness that was above emergent but not meeting minimum score of being innovative. Subjects’ demographic profile had no significant effect on technology integration and pedagogical innovations. Organisation and faculty’s beliefs were found to exert mild positive effect on subjects’ technology integration and pedagogical innovations. Multiple linear regression analysis revealed the direct relationship between technology integration and pedagogical innovations. Hierarchical regression analysis further revealed the enhancement of relationship with the presence of mediating variables for the independent and dependant variables. From the findings of this study, a relationship model for technology integration as the main predictor for faculty member’s pedagogical innovations was proposed. Supportive plans and policies that form the strategies of technology integration within the faculty were found to be a positive mediator that enhanced the relationship between technology integration and pedagogical innovations. Universities had different pedagogical profiles based on ownership and there should be a national policy for technology driven education. This study concluded with a model of relationship for technology integration and pedagogical innovations that paved ways for further research in technology integration and pedagogical innovations in Malaysian higher education institutions.